Infectious Middle East Respiratory Syndrome Coronavirus Excretion and Serotype Variability Based on Live Virus Isolates from Patients in Saudi Arabia - Muth, Doreen (J Clin Microbiol, 2015)
The newly emerged Middle East respiratory syndrome coronavirus (MERS-CoV) has infected at least 1,082 people, including 439 fatalities. So far, no empirical virus isolation study has been done to elucidate infectious virus secretion or serotype variability. Here, we used 51 respiratory samples from 32 patients with confirmed MERS-CoV infection for virus isolation in Vero B4 and Caco-2 cells. We found Caco-2 cells to significantly enhance isolation success over routinely used Vero cells. Isolation success correlated with viral RNA concentration and time after diagnosis as well as with the amount of IgA antibodies secreted in respiratory samples used for isolation. Results from plaque reduction neutralization assays using a representative range of serum samples and virus isolates suggested that all circulating human MERS-CoV strains represent one single serotype. The choice of prototype strain is not likely to influence the success of candidate MERS-CoV vaccines. However, vaccine formulations should be evaluated for their potential to induce IgA.